HPLC and TLC chromatographic methods for simultaneous determination of binary mixture of isoconazole nitrate and diflucortolone valerate - Mohamed R. El-Ghobashy; Yasmin M. Fayez; Zeinab M. Goda; Mostafa A. Shehata (Bulletin of Faculty of Pharmacy Cairo University, 2016)
HPLC and TLC-densitometric methods were used to determine a binary mixture of isoconazole (ISO) and diflucortolone (DIF). For HPLC method a rapid separation could be achieved on a C18 column using mobile phase of 80% acetonitrile–20% methanol. The components were monitored at 230 nm over a concentration range of 10–90 μg mL−1 for ISO and 2–18 μg mL−1 for DIF with mean percentage recoveries 99.95 ± 0.866 and 99.98 ± 0.744, respectively. The second method is TLC-densitometric, where ISO and DIF are separated on silica gel plates using ethyl acetate: chloroform: toluene (60:10:10 by volume) as a developing system and scanning of the separated bands at 215 nm over a concentration range of 0.1–4 μg spot−1 for ISO and scanning of the separated bands at 237 nm over a concentration range of 0.1–1.4 μg spot−1 for DIF with mean percentage recoveries 100.19 ± 0.956 and 100.1 ± 0.689 for ISO and DIF, respectively. The suggested methods were used to determine both drugs binary mixture in pure form and dosage form. The validity of the proposed methods was further assessed by applying standard addition technique. The obtained results were statistically compared with official HPLC method, showing no significant difference with respect to accuracy and precision.